Analisis desain formulir registrasi pasien untuk meningkatkan optimasasi dokumentasi rekam medis di BPM Siti Asnah Bantul - Sevtiyani , Imaniar; Ariningtyas, Ristiana Eka (Sahabat Publikasi Kuu, 2022)
Improving the quality of services is currently a demand for all health facilities, including health services carried out by Siti Asnah Independent Practice Midwife (BPM) located in Bantul Regency. Improving the quality of services can be started with efforts to improve the documentation of medical record files, one of which is by using patient registration forms. The patient registration form contains data and information about the patient's identity which can be used as a basis for providing actions / services so that the actions provided to patients at BPM Siti Asnah Bantul Regency can be carried out appropriately, effectively and efficiently. However, currently BPM Siti Asnah Bantul Regency does not have a patient registration form so that patient data cannot be documented properly. The purpose of this study was to design a patient registration form at BPM Siti Asnah Bantul Regency. This research is a qualitative research with action research method. This research starts from the primary data collection stage with the interview method conducted to patients and health workers at BPM Siti Asnah Bantul and observation, then proceeds with the patient registration form design stage. The next stage is the implementation stage and trial and evaluation to then improve the form design. The results of this study indicate that there is no registration form at BPM Siti Asnah Bantul. The registration process is only done by recording the patient's identity on a piece of paper every time the patient comes to visit. The design of the patient registration form at BPM Siti Asnah Bantul uses HVS A4 paper a paper weight of 70 grams with black ink. The design of the registration form carried out in this study has been based on the minimum standards contained in Permenkes No.289 of 2008 in the physical, anatomical and content aspects.